5G mobile core network : design, deployment, automation, and testing strategies - Shetty, Rajaneesh Sudhakar (Apress, 2021)
Get up to speed on 5G and prepare for the roll out of the next generation of mobile technology. The book begins with an introduction to 5G and the advanced features of 5G networks, where you'll see what makes it bigger, better, and faster. You will learn 5G NSA and SA packet core design along with some design challenges, taking a practical approach towards design and deployment. Next, you will understand the testing of the 5G packet core and how to automate it. The book concludes with some advanced service provider strategies, including architectural considerations for service providers to enhance their network and provide services to non-public 5G networks. 5G Mobile Core Network is intended for those who wish to understand 5G, and also for those who work extensively in a service provider environment either as operators or as vendors performing activities such as network design, deployment, testing, and automation of the network. By the end of this book you will be able to understand the benefits in terms of CAPEX and OPEX while considering one design over another. Consulting engineers will be able to evaluate the design options in terms of 5G use cases, the scale of deployment, performance, efficiency, latency, and other key considerations. What You Will Learn Understand the life cycle of a deployment right from pre-deployment phase to post-deployment phase See use cases of 5G and the various options to design, implement, and deploy them Examine the deployment of 5G networks to large-scale service providers Discover the MVNO/MVNE strategies that a service provider can implement in 5G Who This Book Is For Anyone who is curious about 5G and wants to learn more about the technology.